The Storyboards for the Development of VRS-Based Laboratory Learning in the Cardiovascular System - Sri Suparti; Susana Widyaningsih; Jebul Suroso (Future Science, 2022)
Clinical and laboratory learning is imperative in achieving the competency target of nursing students. Due to the COVID-19 pandemic, learning must be done online; therefore, the practice of laboratory and clinical learning could only be conducted somewhat. The development of virtual learning media that minimizes face-to-face and represents clinical and laboratory situations is urgently needed nowadays. This research aims to develop a VRS storyboard as the media for learning cases of the cardiovascular system. This research followed Research and Development (R&D), which were shortened into 5 steps (literature review, concept creation, concept model development, model testing and evaluation, and content model evaluation). The storyboard and case framework was developed from the results of FGDs and workshops and based on the NLN/ Jeffries Simulation model. The study's findings indicate the availability of nursing care storyboards about cases of Cardiovascular Disorders for student simulations based on best nursing practices consisting of learning objectives, scenes, actions, challenges, and elements of transfer, as well as opportunities to ask questions. The storyboard format allows interactive learning in terms of material, practice in nursing care skills, and nursing actions in a safe and immersive environment during the COVID-19 pandemic.